Une transition économique inattendue : vers le « cupidalisme » ? - Wladimir Andreff (Revue de la Régulation)
During the last quarter of a century various activities of asset grabbing hinder capital accumulation in the legal and regulated part of the real economy and finance. Originating in post-communist economies in transition asset grabbing has spread throughout the global economy through public assets transferred to private owners (privatisations), predatory real assets stripping by finance, the emergence of shadow finance (of which shadow banking), namely in all the black holes of global finance (tax and judiciary havens). Asset grabbing relies on bad practices such as the under-estimation of asset value, asset tunneling, price and rate manipulations in financial markets, short selling, a systematic lending to insolvents, financial pyramids, fraud, swindling and even economic crime. It is conducted in breaching formal rules of capitalism. A systemic greed underlies these strategies of relative wealth maximisation, though maximizing it without any constraint, of which asset grabbing is a rational tool, in a winner-take-all economy.A “systemic greed” sector of the economy is theoretically conceived which gathers all asset grabbing activities, alongside with a capitalist sector. In absence of published data about asset grabbing a preliminary estimation of this sector is provided. Its emergence generates new forms of competition, state capture by oligarchs, and an inconsistent economic regime plagued with unbalanced, slow and unstable growth, and crises resulting from a “struggle between two regulators”, as it is typical in a transition economy. The conclusion briefly maps out a few economic policy measures that are urgently needed for hedging against the development of the “systemic greed” sector.